ERP Correlates of Performance Monitoring: a Mouse-Tracking Study - V.A. Medvedev; K.E. Sayfulina; A.M. Rytikova; B.V. Chernyshev (Экспериментальная психология, 2020)
Performance monitoring involves detection of action outcomes and initiation of appropriate behavioral adaptations. Psychophysiological mechanisms of performance monitoring remain largely understudied in the context of uncertainty that arises at the stage of stimulus identification and decision making, as well as in the context of inhibition/correction of the motor response. In the current study, we investigate relations between behavioral performance measures and several ERP components: N2, ERN/CRN and Pe. Participants performed a condensation task and made their responses by moving mouse cursor. Response registration using mouse tracking allowed us to obtain two independent behavioral measures: mouse movement initiation time and movement duration. Amplitude of N2 and CRN was dependent on movement initiation time: N2 was increased and CRN was decreased for ‘late’ correct responses compared with ‘early’ correct ones; this finding is compatible with the explanation that ‘late’ responses involve higher pre-response conflict and higher uncertainty compared with ‘early’ ones. Movement duration time was a novel independent behavioral parameter, that cannot be measured using traditional keystrokes. This behavioral measure was related to the early Pe: its amplitude was more positive for ‘long’ responses compared with ‘short’ ones. This finding may be explained by mechanisms of an ongoing response inhibition. We suggest that this effect is linked to response stopping, which may be related to outcome awareness.